Still Alice [large type] : a novel - Genova, Lisa (Large Print Press, a part of Gale, Cengage Learning, 2015)
Feeling at the top of her game when she is suddenly diagnosed with early onset Alzheimer's disease, Harvard psychologist Alice Howland struggles to find meaning and purpose in her life as her concept of self gradually slips away.